2005
DOI: 10.1081/ss-200059594
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Solvent Extraction of Ra(II) and Ba(II) from Aqueous Solutions with Lipophilic, Acyclic, Di‐ionizable Polyethers

Abstract: Twelve lipophilic, acyclic polyethers, each with two terminal N-(X)sulfonyl carboxamate groups, are found to efficiently extract Ra(II) and Ba(II) at radiotracer levels from aqueous solution into chloroform. With the presence of Ba(II) carrier in the aqueous feed solution, very appreciable Ra(II)/Ba(II) selectivity is observed in single-stage, liquid-liquid extraction for the polyether that combines the largest polyether pseudo-cavity and the most acidic ionizable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Comparison of the results shown by curve flotation (Figure 6). Similar conclusions were obtained by Walkowiak et al [42], which investigated the separation of Ra 2+ and Ba 2+ from aqueous solutions using ionizable acyclic polyethers (4-11, 12, 13) by competitive solvent extraction in a liquid-liquid, presented in Table 3. It was The best degrees of separation of Ba 2+ were obtained at pH 9.…”
Section: Effect Of Phsupporting
confidence: 84%
See 1 more Smart Citation
“…Comparison of the results shown by curve flotation (Figure 6). Similar conclusions were obtained by Walkowiak et al [42], which investigated the separation of Ra 2+ and Ba 2+ from aqueous solutions using ionizable acyclic polyethers (4-11, 12, 13) by competitive solvent extraction in a liquid-liquid, presented in Table 3. It was The best degrees of separation of Ba 2+ were obtained at pH 9.…”
Section: Effect Of Phsupporting
confidence: 84%
“…Similar conclusions were obtained by Walkowiak et al [42], which investigated the separation of Ra 2+ and Ba 2+ from aqueous solutions using ionizable acyclic polyethers (4-11, 12, 13) by competitive solvent extraction in a liquid-liquid, presented in Table 3. It was Similar conclusions were obtained by Walkowiak et al [42], which investigated the separation of Ra 2+ and Ba 2+ from aqueous solutions using ionizable acyclic polyethers (4-11, 12, 13) by competitive solvent extraction in a liquid-liquid, presented in Table 3. It was found that with the increase in pH, the Ba 2+ extraction degree increases.…”
Section: Effect Of Phsupporting
confidence: 84%